Study management and maintenance of irrigation system by farmers in Borikan District, Borikhamxay Province - PHILAKUNE, Souladeth; SIVANHPHENG, Oular; PHILAKOUNE, Soulasith; SITAVONG, Saykham (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
From summarizing and analyzing the data of a sample group of 31 farmers, according to the purpose of the study to evaluate the ability to implement the management - self-use of the irrigation system in Phuhomxay Village, Borikan District, Borikhamxay Province. It can be seen that: the irrigation water user group of Phuhomxay Village has the ability to manage and use the irrigation system that they manage themselves well in some areas and still need to improve in some areas. The purpose of this study is to study the irrigation system management capacity of the irrigation water user group of the irrigation project in Phuhomxay Village, Borikan District, Borikhamxay Province. The second-hand data collection was studied from the documents, the report of Nam Neng 1 irrigation project and from the irrigation staff of Borikan district, the village chief of Phuhomxay village and from the annual report of the water user group committee and the first-hand data collection is the field data collection, based on the actual situation of the sample group (of the water user group members). This data analysis is analyzing quantitative and qualitative data side by side using statistical data and comments from the sample group in terms of percentage in the analysis will use Microsoft Office Excel as an analysis tool. From the study, it can be seen that: the irrigation water user group in Phuhomxay Village has the ability to manage and use the irrigation system that they manage well in some areas and still need to improve in some areas.